Organizational Impact of an ID NOW™ COVID-19 Point-Of-Care Testing for SARS-Cov2 Detection in A Maternity Ward - Van, Jean-Claude Nguyen; Pilmis, Benoit; Khaterchi, Amir; Billuart, Olivier; Ponfilly, Gauthier Péan De; Monnier, Alban Le; Azria, Elie; Mizrahi, Assaf (Archives of Clinical and Biomedical Research, 2023)
Background: SARS-CoV-2 has been responsible for more than 676 million cases of COVID-19 worldwide. RT-PCR is considered the “gold standard” for the diagnosis of patients suspected of having COVID-19. During the heightened waves of the pandemic, more rapid tests have been required. Point-of-care tests (POCT) for COVID-19 include antigen tests, serological tests, and other molecular-based platforms. The ID NOW™ COVID-19 assay (Abbott) performs an isothermal gene amplification of a target encoding the RNA-dependent RNA polymerase of SARSCoV-2. The main objective of this study was to evaluate the organizational impact following the implementation of a POC testing platform ID NOW™ in a maternity ward. Materials and Methods: This retrospective study included pregnant women admitted for Groupe Hospitalier Paris Saint-Joseph Paris. The study was conducted over 2 periods lasting 6 months each. The first period (P1) corresponded to the 2nd wave in France (July to December 2020) whereas the second (P2) period focused on the 3rd wave (February to July 2021). During P1, viral detection was performed by RT-PCR at the hospital’s laboratory. During P2, it was performed with the ID NOW™ COVID-19 test directly in the delivery room by nursing staff after training and certification. Our primary endpoint was the length of time in the birth room from admission to discharge in the postpartum period. Results: 2447 pregnant women were included, 1053 during P1 and 1394 during P2. The median age, percentage of singleton pregnancies, mean gestational age, percentage of nulliparous individuals, percentage of vaginal deliveries, and COVID19 positivity rate were comparable between the two periods. During P2, the length of stay in the delivery room was significantly shorter than during P1 (17.9 vs 14.7 hours, p<0.001). Conclusion: Analysis of the data from this study following the implementation of the ID NOW™ POCT in the maternity ward indicates a significant decrease in the length of stay in the birth room. This outcome needs to be confirmed in a multicenter cohort, in particular to precise the specific impact of COVID-19 care on delays.